A.
\(\left[ \begin{array}{l}
x = - \frac{\pi }{6} + k2\pi \\
x = \frac{\pi }{6} + k2\pi
\end{array} \right.\)
B.
\(\left[ \begin{array}{l}
x = \frac{\pi }{6} + k2\pi \\
x = - \frac{\pi }{2} + k2\pi
\end{array} \right.\)
C.
\(\left[ \begin{array}{l}
x = - \frac{\pi }{6} + k2\pi \\
x = - \frac{\pi }{2} + k2\pi
\end{array} \right.\)
D.
\(\left[ \begin{array}{l}
x = \frac{\pi }{2} + k2\pi \\
x = \frac{\pi }{6} + k2\pi
\end{array} \right.\)
D
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247